Imbalance of SMC1 and SMC3 Cohesins Causes Specific and Distinct Effects - Laugsch, Magdalena (Public Library of Science, 2013)
SMC1 and SMC3 form a high-affinity heterodimer, which provides an open backbone of the cohesin ring, to be closed by a kleisin protein. RNAi mediated knock-down of either one heterodimer partner, SMC1 or SMC3, is expected to cause very similar if not identical phenotypes. However, we observed highly distinct, protein-specific phenotypes. Upon knock-down of human SMC1, much of SMC3 remains stable, accumulates in the cytoplasm and does not associate with other cohesin proteins. Most of the excess nuclear SMC3 is highly mobile and not or only weakly chromosome-associated. In contrast, human SMC3 knock-down rendered SMC1 instable without cytoplasmic accumulation. As observed by differential protein extraction and in FRAP experiments the remaining SMC1 or SMC3 proteins in the respective SMC1 or SMC3 knock-down experiments constituted a cohesin pool, which is associated with chromatin with highest affinity, likely the least expendable. Expression of bovine EGFP-SMC1 or mouse EGFP-SMC3 in human cells under conditions of human SMC1 or SMC3 knock-down rescued the respective phenotypes, but in untreated cells over-expressed exogenous SMC proteins mis-localized. Paucity of either one of the SMC proteins causes RAD21 degradation. These results argue for great caution in interpreting SMC1 and SMC3 RNAi or over-expression experiments. Under challenged conditions these two proteins unexpectedly behave differently, which may have biological consequences for regulation of cohesin-associated functions and for human cohesin pathologies.